CUSTOMER INTEREST IN USING MANDIRI M-BANKING: CAN EASE OF USE, TRUST, INFORMATION TECHNOLOGY READINESS, AND SOCIAL FACTORS AFFECT IT? - Maydelyn Goh; Evelyn Wijaya; Achmad Tavip Junaedi; Agus Hocky (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
Changes in information technology have encouraged banks to provide easy access to information services for their customers in conducting transaction processes by launching electronic banking services. This study aimed to analyze the effect of ease of use, trust, information technology readiness, and social factors on customer interest in using Mandiri M-Banking. The research population was M-banking users of Mandiri Bank at the Pekanbaru Branch Office with a sample size of 120 people. Research analysis method was multiple linear regression analysis using SPSS 21. The results showed a positive and significant relationship between trust and information technology readiness on customer interest in using Mandiri M-banking. While ease of use and social factors did not significant on customer interest in using Mandiri M-banking.